What Can a Cerebral Hemorrhage Hide? - Vaz, Ana; Serviço de Medicina Física e de Reabilitação, Centro Hospitalar Universitário de São João, Porto, Portugal (2022)
Non-traumatic cerebral hemorrhages are less common than acute ischaemic vascular lesions but are associated with higher mortality rates and years of life lost due to disability. They may lead to a diversity of neurological deficits, being the intervention of Physical Medicine and Rehabilitation (PMR) essential for clinical and functional improvement.59 years-old female patient, non-hypertense, previously independent in activities of daily living and cognitively intact. The patient was admitted to the Emergency Department after a sudden severe headache. On admission, the patient presented a left homonymous hemianopsia and hemiparesia. Computed tomography revealed a voluminous parenchymal cortico-subcortical right temporo-fronto- parietal hemorrhage. The patient underwent emerging decompressive craniectomy. During hospitalization, the patient had a positive clinical and functional evolution, and was transferred on the 66th day of hospitalization to the PMR ward. After 17 days, the patient presented an indolent deterioration of the state of consciousness, with progressive somnolence and prostration, making unfeasible to participate in the rehabilitation program. Given the worsening of the neurological status, neuro-imaging study was repeated and a large expansive lesion with necrotic- cystic enhancement pattern, of probable neoplastic etiology (primary glial or secondary series) was depicted.The evaluation, interpretation and orientation of cases of nontraumatic intracerebral hemorrhage with fluctuation of neurological status and/or stagnation of functional evolution in the subacute and chronic phase appears as a diagnostic challenge. It is essential to increase the perception that intracerebral hemorrhage without defined etiology may be due to primary or secondary brain neoplasms, which require early and directed evaluation and guidance.